Rhinacanthus nasutus leaf improves metabolic abnormalities in high-fat diet-induced obese mice - Supaporn Wannasiri; Pritsana Piyabhan; Jarinyaporn Naowaboot (Asian Pacific Journal of Tropical Biomedicine, 2016)
Objective: To investigate the effect of Rhinacanthus nasutus (R. nasutus) leaf extract on impaired glucose and lipid metabolism in obese ICR mice. Methods: Obesity was induced in the male ICR mice by feeding them a high-fat diet (60 kcal% fat) for 12 weeks. After the first six weeks of the diet, the obese mice were administered with the water extract of R. nasutus leaves at 250 and 500 mg/kg per day for the next six weeks. Subsequently, the blood glucose, lipid profiles, insulin, leptin, and adiponectin levels were measured. The liver and adipose tissues were excised for histopathological examination and protein expression study. Results: After six weeks of the treatment, R. nasutus extract (at 250 and 500 mg/kg per day) was found to reduce the elevated blood glucose level, improve the insulin sensitivity, decrease the serum leptin, and increase the serum adiponectin levels. The obese mice treated with R. nasutus were found to have a reduction in the increased lipid concentrations in their serum and liver tissues. Moreover, treatment with R. nasutus reduced the fat accumulation in the liver and the large adipocyte size in the fat tissues. Interestingly, the administration with R. nasutus extract was marked by an increase in the hepatic peroxisome proliferators-activated receptor alpha, fat cell adiponectin, and glucose transporter 4 proteins. Conclusions: To the best of our knowledge, the present study is the first report on the impact of R. nasutus extract in improving the impaired glucose and lipid metabolism in high-fat diet-induced obesity in mice via stimulating the insulin sensitivity in the liver and adipose tissues.